Design and Impact of Individual Learning Modifications on Self-Efficacy of Students with Mental Disability - Nirwaningtyas, Fitria; Nuriadin, Ishaq; Fetrimen (Global Synthesis in Education Journal, 2025)
This study aims to design and evaluate the impact of individual learning modifications on the self-efficacy of students with mental disabilities at SDN Semper Barat 07. The research was conducted using a quasi-experimental pretest–posttest design involving 12 students identified with mild to moderate cognitive disabilities. Learning modifications were developed through needs assessment, teacher consultation, and adaptation of instructional materials, focusing on pacing adjustments, visual supports, and simplified task structures. Self-efficacy was measured using an adapted scale validated for primary-level special education contexts. Data were collected before and after an eight-week intervention and analyzed using paired sample t-tests, supported by qualitative classroom observations. The results showed a statistically significant increase in students' self-efficacy scores (p < 0.05) with notable improvements in confidence, task persistence, and willingness to participate in class activities. Qualitative findings indicated that the modifications enhanced engagement and reduced learning anxiety. These results suggest that individualized learning modifications can be an effective approach to strengthening self-efficacy among students with mental disabilities in inclusive primary school settings. With such strategies, educators can foster more equitable participation and academic growth, supporting inclusive education goals in Indonesia.